2020
DOI: 10.1111/liv.14766
|View full text |Cite
|
Sign up to set email alerts
|

A case series analysis of serious exacerbations of viral hepatitis and non‐viral hepatic injuries in tocilizumab‐treated patients

Abstract: Background and Aims Reports of moderate to severe liver injury associated with tocilizumab, an interleukin‐6 (IL‐6) receptor antagonist, have been reported in the post‐marketing setting. This case series aims to characterize cases of tocilizumab‐associated clinically significant hepatic injury. Methods We analysed cases of severe acute liver injury associated with tocilizumab reported in the FDA Adverse Event Reporting System and the medical literature. Results We identified 12 cases in which tocilizumab was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As a result, the reporting of HBV reactivation in HBsAg + patients was limited. Nonetheless, cases of HBV flares, including fatal ones, have been reported in RA patients who are HBsAg + following treatment with tocilizumab [ 36 , 37 ]. In our systematic review, only three studies involving HBsAg + patients receiving TCZ were identified, with a total sample size of 25 individuals [ 17 , 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the reporting of HBV reactivation in HBsAg + patients was limited. Nonetheless, cases of HBV flares, including fatal ones, have been reported in RA patients who are HBsAg + following treatment with tocilizumab [ 36 , 37 ]. In our systematic review, only three studies involving HBsAg + patients receiving TCZ were identified, with a total sample size of 25 individuals [ 17 , 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…If similar studies are conducted on EBV in the future, it may be possible to prove the direct impact of TCZ. At present, there is only one reported case of TCZ reactivation of EBV ( 24 ) in a patient with viral hepatitis. TCZ should thus be administered with caution, with consideration for its potential effects on other viruses.…”
Section: Discussionmentioning
confidence: 99%
“…More data on HBVr following tocilizumab therapy exist from its established use in RA. Case reports of serious and even fatal HBV flares in HBsAg-positive patients with RA after tocilizumab have been described [ 46 , 47 ]. As such antivirals are often commenced in these patients prior to treatment, thus limiting their representation in the literature.…”
Section: Impact Of Covid-19 Treatments On Hbvr–non-corticosteroid Drugsmentioning
confidence: 99%